A study on collaboration innovation: Perspectives of innovative ecosystems of value co-creation using evolutionary game theory - Xiaowei Shi; Jifa Wang (PLoS ONE, 2026)
Enhancing emphasis on value co-creation and optimizing resource allocation are crucial for fostering deep coupling and synergistic development within innovation ecosystems, thereby enhancing innovation efficacy. Within a bounded rationality framework, this study constructs an evolutionary game model of value co-creation behavior between core enterprises and participating firms in innovation ecosystems. Simulation analysis reveals the underlying evolutionary dynamics. Findings indicate that sufficient resource reserves, superior value creation capabilities, positive cognitive attitudes, effective incentive policies, and appropriate regulatory measures all facilitate high-quality value co-creation. Conversely, heightened uncertainty risks and substantial co-creation costs may impede value co-creation among innovation actors within the ecosystem. The results hold significant implications for optimizing value co-creation mechanisms and promoting the healthy development of innovation ecosystems.